Building a bridge between adaptive capacity and adaptive potential to understand responses to environmental change. (31st March 2021) - Seaborn, Travis; Griffith, David; Kliskey, Andrew; Caudill, Christopher C.
Abstract: Adaptive capacity is a topic at the forefront of environmental change research with roots in both social, ecological, and evolutionary science. It is closely related to the evolutionary biology concept of adaptive potential. In this systematic literature review, we: (1) summarize the history of these topics and related fields; (2) assess relationship(s) between the concepts among disciplines and the use of the terms in climate change research, and evaluate methodologies, metrics, taxa biases, and the geographic scale of studies; and (3) provide a synthetic conceptual framework to clarify concepts. Bibliometric analyses revealed the terms have been used most frequently in conservation and evolutionary biology journals, respectively. There has been a greater growth in studies of adaptive potential than adaptive capacity since 2001, but a greater geographical extent of adaptive capacity studies. Few studies include both, and use is often superficial. Our synthesis considers adaptive potential as one process contributing to adaptive capacity of complex systems, notes "sociological" adaptive capacity definitions include actions aimed at desired outcome (i.e., policies) as a system driver whereas "biological" definitions exclude such drivers, and suggests models of adaptive capacity require integration of evolutionary and social–ecological system components. Abstract : Adaptive capacity is at the forefront of environmental change research but definitions and uses are varied. The broadest definitions encompass social–ecological systems where human perception and intent can affect system dynamics, whereas the adaptive capacity of biological systems lacks teleological effects. Both adaptive capacity concepts integrate adaptive potential with environmental change, plasticity, and dispersal, while accounting for feedback loops of potential selective pressures. Through literature review, we find few studies include both, and use is often superficial. A key future challenge is identifying and measuring drivers and feedbacks of system capacity, particularly the key connections between social and ecological systems.